Evaluating the Root Canal Morphology of Permanent Maxillary First Molars in Iranian Population - Rezaeian, Mohsen; Rouhani Tonekaboni, Maryam; Iranmanesh, Foad (Iranian Endodontic Journal, 2019)
Introduction: A successful endodontic treatment depends on a comprehensive knowledge of the morphology of canal and its variations, an appropriate access cavity, proper cleaning and shaping and adequate root canal filling. The present study was carried out to evaluate the root canal morphology of permanent maxillary first molars in an Iranian population. Methods and Materials: In this in vitro study, 80 extracted permanent maxillary first molars from a population in Rafsanjan, Iran were collected. Root canal morphology was evaluated by clearing technique under stereomicroscope under 40× magnification. A combination of Vertucci’s and Sert and Bayirli’s classifications were used to determine the root canal types. Data were analyzed by SPSS 18 software using descriptive statistics. Results: All palatal roots and almost all distobuccal roots had type I configuration. Ten different types of root canal system were found in mesiobuccal roots, among which type I was the most common (38.75%), followed by type II, IV, V, VI, IX, XV, XVI=XIX and VII, respectively. Conclusion: The mesiobuccal roots of permanent maxillary first molar had the most complex root configuration. Keywords: Maxillary First Molar; Root Canal Anatomy; Root Morphology